Development of a Manipulator System for X-ray Imaging Laminography (ELEKTRIKA- Journal of Electrical Engineering, 2021)
X-ray imaging laminography is a well-known non-destructive testing (NDT) technique well suited for non-destructive examination of large and flat structures of which traditional computed tomography (CT) is impractical. This technique allows for precise characterisation of welding defects, including its depth information, in welded components, ensuring component quality meets the standard criteria and safety purposes. This work highlights an approach to develop and establish a new manipulator system for the x-ray imaging laminography to characterise the welding defects in high-quality radiographed images. The mechanical hardware and programmed software system are developed with synchronisation to well established Radiographic Testing – Digital (RT-D) software in acquiring the image. To ensure compliance with industry standards, the exposure conditions, image sensitivity, and quality are analysed according to ISO 17636-2.